Potensi Lerak Sebagai Bahan Dasar Pembuatan Sabun: Studi Formulasi dan Evaluasi di Desa Lebung Nala Kecamatan Ketapang - Oktaviani, Nia; Nabila, Annisa Dwi; Hayati, Afifah Hany; Datunnisa, Rau (WISE Pendidikan Indonesia, 2024)
This study explores the potential of Sapindus rarak (soapberry) as a base ingredient for environmentally friendly detergent production in Lebung Nala Village, Ketapang District. By involving 15 local community members, particularly women from the PKK (Family Welfare Movement), the research implemented a series of socialization and training activities focused on producing natural detergents using lerak. The study applied a qualitative descriptive approach to analyze the environmental, health, and socio-economic impacts of using lerak-based detergents. The findings indicate that the initiative not only increased participants’ awareness of the harmful effects of chemical detergents but also improved their practical skills and opened up local business opportunities. The process of making natural soap was well received and applicable in everyday household activities. Overall, the research highlights that lerak-based detergents offer a sustainable alternative that integrates environmental protection with community empowerment.